Optimizing the mnemonic similarity task for efficient, widespread use - Stark, Craig E. L.; Noche, Jessica A.; Ebersberger, Jarrett R.; Mayer, Lizabeth; Stark, Shauna M. (Frontiers in Behavioral Neuroscience, 2023)
The Mnemonic Similarity Task (MST) has become a popular test of memory and, in particular, of hippocampal function. It has been heavily used in research settings and is currently included as an alternate outcome measure on a number of clinical trials. However, as it typically requires ~15 minutes to administer and benefits substantially from an experienced test administrator to ensure the instructions are well-understood, its use in trials and in other settings is somewhat restricted. Several different variants of the MST are in common use that alter the task format (study-test vs. continuous) and the response prompt given to participants (old / similar / new vs. old / new). Here, we sought to address three main goals: 1) To determine whether a robust version of the task could be created that could be conducted in half the traditional time; 2) To determine whether the test format or response prompt choice significantly impacted the MST’s results; and 3) To determine how robust the MST is to repeat testing. In 7 online experiments in which the same subjects received both the traditional and alternate forms of the MST, we found that test format had no effect on the reliability of the MST, but that shifting to the two-choice response format significantly reduced its ability to reflect the traditional MST’s score. We also found that the full running time could be cut it half or less without appreciable reduction in reliability. We confirmed the efficacy of this reduced task in older adults as well. In these data and an 8th experiment designed to test this directly, we found that while there often are no effects of repeat-testing, small effects are possible, but appear limited to the initial testing session. Finally, we make this optimized version of the task (oMST) freely available for web-based experiment delivery.